Catheter Fracture and Embolization Related to an Arm Venous Port - Brent E. Burbridge (Case Reports in Radiology)
This 55-year-old female had a chest X-ray during a follow-up visit for the management of her breast cancer. The chest X-ray demonstrated an embolized venous catheter superimposed upon the mediastinum. It was determined that the catheter of the patient's arm port had fractured and embolized to the pulmonary circulation. The catheter was retrieved, in the interventional radiology suite, under fluoroscopic guidance. The patient suffered no ill effects. Subsequently, one day later, the old vein port was removed and a new arm port and associated catheter were implanted to facilitate the delivery of the patient's ongoing chemotherapy.